(untitled) (Journal of Environmental Science and Natural Resources, 2015)
The study was conducted to investigate the iron (Fe) contamination in groundwater at Tangail municipality during the period from January to June 2011. Groundwater samples were collected from 18 locations, where 15 were tube-wells, 2 deep tube-wells and 1 pump. The result of the study showed that the highest level of Fe (24.50 mg/l) was found at Dewla north, while the lowest level (1.03 mg/l) was recorded from Bepari para. The highest and lowest amount of Fe was found in ward 1 and 4, respectively. The results were compared with the Bangladesh drinking water quality standards as well as with the international standards. In Bangladesh, permissible limit of Fe is 0.3-1.0 mg/l, whereas WHO standard level is 0.3 mg/l. All the samples were exceeded the standard levels of Fe, whereas ward 1, 2 and 7 were worstly affected. The study also reveal that the availability of Fe does not depend on the type of water sources, but it depends on the aquifers or water table. If the aquifer contains Fe, then the tube-well water will contain Fe or vice versa. These higher Fe concentrations found in the study area may be harmful for those families who are consuming the water from these sources on regular basis. Thus, to overcome this problem the consumers should not drink these higher amounts of Fe, and they should find other sources or replace the tube-well or treat the water before drinking and other domestic and household purposes. DOI: http://dx.doi.org/10.3329/jesnr.v6i1.22051 J. Environ. Sci. & Natural Resources, 6(1): 117-121 2013